Vzpostavitev, nadgradnja in vzdrževanje območij enake bonitete - Košir, Janez (Geodetski vestnik, 2022)
The beginnings of the agricultural and woodland valuation in Slovenia date back to the time of the Austro-Hungarian state when the cadastral classification of land was established. After 1953, the conditions of land management and taxation in Slovenia changed. Expert groups and individuals prepared proposals of land valuation based on site productivity and the economics of the land management. With the publishing of the rules for soil assessment in 1984, the first professional conditions for a new land evaluation were established. The land-rating measures land site productivity based on natural factors, including soil characteristics, climate, relief, and special impacts. The basic unit of administering land rating is the equal land-rating area. The establishment and upgrading took place over several years in the entire territory of Slovenia. The uniform layer of the equal land-rating area of the whole state is administered by the Surveying and Mapping Authority based on the proposal of the individual or ex officio. The uniform layer of equal land-rating area and database of land-rating values are public and used for land valuation purposes and for land management measures.
Keywords: boniteta zemljišč; gozdna zemljišča; katastrska klasifikacija; kmetijska zemljišča; območje bonitete; proizvodna sposobnost; vrednotenje zemljišč